(untitled) (Journal of the College of Basic Education, 2023)
The governorates of the country are witnessing a great difference in their health service capabilities, and in an attempt to reduce this existing disparity and make these capabilities similar between the governorates of the country, and in an effort to accelerate the process of development. Data were taken for the governorates of Iraq, except for the governorates of the northern region, because they were not available. The study included (39) variables in this field to find out the similarities between the governorates in providing services and to know the best methods used in cluster analysis to enable the relevant authorities to develop a plan and study to improve and develop the governorates in which there is a slowdown. In this field, identifying deficiencies and working to improve performance and advance the status of health services in the country. Therefore, the (hierarchical) cluster analysis methods were applied and the best methods of hierarchical cluster analysis were known to reach the best governorate in the provision of health services. In which the research worked, the hierarchical linkage method (Ward’sMethod)) is the best method used because it has the lowest value of the scale according to the scale of the contracted relationship.Some hierarchical methods gave the same interpretation of the results, despite the different levels of coalescence.